2011
DOI: 10.1017/s0007114511005976
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo intestinal studies on calcium and phosphate transport in growing goats fed a reduced nitrogen diet

Abstract: In ruminant feeding, the reduction of dietary protein is an effective approach for decreasing the excretion of N. In non-ruminant species, the intestinal absorption of Ca was affected when dietary protein was reduced. Therefore, it was the aim of the present study to characterise the intestinal absorption of Ca and inorganic phosphate (P(i)) in goats fed different N and Ca diets. Intestinal flux rates of Ca and P(i) were determined in goats fed a reduced N and Ca diet by Ussing chamber experiments. For a more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
3
9
0
Order By: Relevance
“…A reduction of dietary N led to decreased expression of the apical Ca channel TRPV6 revealed by two-way ANOVA and in combination with a reduced dietary Ca supply led to significantly decreased expression compared with solitary Ca reduction, whereas the latter stimulated TRPV6 expression in all the intestinal segments. These findings were in accordance with results from studies with young goats fed a simultaneous N-and Ca-reduced diet, showing reduced TRPV6 expression in mid-jejunum (11) , and adult goats on a Ca-restricted diet having increased expression levels of TRPV6 (12) . Expression of the intracellular CaBP D9K diminished in all the intestinal segments due to the reduced dietary N content.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A reduction of dietary N led to decreased expression of the apical Ca channel TRPV6 revealed by two-way ANOVA and in combination with a reduced dietary Ca supply led to significantly decreased expression compared with solitary Ca reduction, whereas the latter stimulated TRPV6 expression in all the intestinal segments. These findings were in accordance with results from studies with young goats fed a simultaneous N-and Ca-reduced diet, showing reduced TRPV6 expression in mid-jejunum (11) , and adult goats on a Ca-restricted diet having increased expression levels of TRPV6 (12) . Expression of the intracellular CaBP D9K diminished in all the intestinal segments due to the reduced dietary N content.…”
Section: Discussionsupporting
confidence: 91%
“…In former studies by Muscher et al (11) , a simultaneous dietary N and Ca reduction led to an increase in intestinal Ca absorption in the mid-jejunum of young goats. This may have been due to a lower body weight gain, and therefore lower Ca requirement of goats, in the control group in this former study, which was then stimulated by reducing the amounts of Ca and N.…”
Section: Discussionmentioning
confidence: 91%
“…Own previous studies have shown that dietary N reduction affected overall Ca homeostasis in young goats leading to a decrease in plasma calcitriol concentrations and intestinal transcellular Ca absorption [ 5 , 6 ]. Additionally, though a single dietary Ca reduction stimulated intestinal Ca absorption in young and adult goats [ 5 , 7 ]; a concomitant reduction in N supply eliminated this stimulating effect in young goats [ 5 , 8 ]. Diminished transcellular Ca absorption in goats fed an N reduction or an N and Ca reduction was associated with reduced plasma calcitriol concentrations as the main regulator of transcellular Ca transport in the small intestine [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Muscher et al have also recently suggested a post-transcriptional regulation of TRPV6 in goats fed a reduced nitrogen and calcium diet. 23 Because there was an inverse relationship between intestinal calcium and iron absorption, 24 the enhanced intestinal iron absorption that was commonly observed in b-thalassemic mice, 12 presumably because of the thalassemia-induced upregulation of DMT1 transcription (Figure 2(A)), could partly explain the decrease in the duodenal calcium transport. The cellular mechanism of the iron hyperabsorption-induced suppression of intestinal calcium absorption remains elusive; however, the elevated intracellular iron concentration has been known to increase reactive oxygen species, which can reduce the PMCA activity.…”
Section: Discussionmentioning
confidence: 99%